Community-acquired and hospital-acquired medication harm among older inpatients and impact of a state-wide medication management intervention. Issue 2 (18th October 2018) - Pellegrin, Karen; Lozano, Alicia; Miyamura, Jill; Lynn, Joanne; Krenk, Les; Jolson-Oakes, Sheena; Ciarleglio, Anita; McInnis, Terry; Bairos, Alistair; Gomez, Lara; Benitez-McCrary, Mercedes; Hanlon, Alexandra
Abstract : Background: We previously reported reduction in the rate of hospitalisations with medication harm among older adults with our 'Pharm2Pharm' intervention, a pharmacist-led care transition and care coordination model focused on best practices in medication management. The objectives of the current study are to determine the extent to which medication harm among older inpatients is 'community acquired' versus 'hospital acquired' and to assess the effectiveness of the Pharm2Pharm model with each type. Methods: After a 3-year baseline, six non-federal general acute care hospitals with 50 or more beds in Hawaii implemented Pharm2Pharm sequentially. The other five such hospitals served as the comparison group. We measured frequencies and quarterly rates of admissions among those aged 65 and older with 'community-acquired' (International Classification of Diseases-coded as present on admission) and 'hospital-acquired' (coded as not present on admission) medication harm per 1000 admissions from 2010 to 2014. Results: There were 189 078 total admissions from 2010 through 2014, 7% of which had one or more medication harm codes. There were 16 225 medication harm codes, 70% of which were community-acquired, among these 13 795 admissions. The varied times when the intervention was implemented across hospitals were associated with a significant reduction in the rate of admissions with community-acquired medication harm compared with non-intervention hospitals (p=0.001), and specifically harm by anticoagulants (p<0.0001) and by medications in therapeutic use (p<0.001). The hospital-acquired medication harm rate did not change. The rate of admissions with community-acquired medication harm was reduced by 4.28 admissions per 1000 admissions per quarter in the Pharm2Pharm hospitals relative to the comparison hospitals. Conclusion: The Pharm2Pharm model is an effective way to address the growing problem of community-acquired medication harm among high-risk, chronically ill patients. This model demonstrates the importance of deploying specially trained pharmacists in the hospital and in the community to systematically identify and resolve drug therapy problems.